Asymmetric distribution of auxin correlates with gravitropism and phototropism but not with autostraightening (autotropism) in pea epicotyls - Haga, Ken (Journal of experimental botany, 2006)
The relationships between the distribution of the native auxin indole-3-acetic acid (IAA) and tropisms in the epicotyl of red light-grown pea (Pisum sativum L.) seedlings have been investigated. The distribution measurement was made in a defined zone of the third internode, using (3)H-IAA applied from the plumule as a tracer. The tropisms investigated were gravitropism, pulse-induced phototropism, and time-dependent phototropism. The investigation was extended to the phase of autostraightening (autotropism) that followed gravitropic curvature. It was found that IAA is asymmetrically distributed between the two halves of the zone, with a greater IAA level occurring on the convex side, at early stages of gravitropic and phototropic curvatures. This asymmetry was found in epidermal peels and, except for one case (pulse-induced phototropism), no asymmetry was detected in whole tissues. It was concluded, in support of earlier results, that auxin asymmetry mediates gravitropism and phototropism and that the epidermis or peripheral cell layers play an important role in the establishment of auxin asymmetry in pea epicotyls. During autostraightening, which results from a reversal of growth asymmetry, the extent of IAA asymmetry was reduced, but its direction was not reversed. This result demonstrated that autostraightening is not regulated through auxin distribution. In this study, the growth on either side of the investigated zone was also measured. In some cases, the measured IAA distribution could not adequately explain the local growth rate, necessitating further detailed investigation